Feasibility Analysis of Sapphire Compound Refractive Lenses for Advanced X-Ray Light Sources - Wang, Yunzhu; Dong, Xiaohao; Hu, Jun (Frontiers in Physics, 2022)
The compound refractive lens（CRL） is a commonly used X-ray optical component for photon beam conditioning and focusing on the beamlines of the X-ray facilities. The normal preparation materials are beryllium, aluminum, silicon of current lenses, and they all suffered from high heat load fatigue and short pulse damage risks. Hard materials based CRL is engaged attention for the advanced X-ray application. Sapphire crystal has the advantages of high density, high melting point, low thermal expansion coefficient. In this paper, properties of the refraction and absorption ratio of Sapphire and parameters of Sapphire lenses of effective aperture, transmittance, resolution, number of lenses needed for a certain focus, are taken into account for the CRL design, comparing with those of several common materials as well. The calculation results show that the performance of the sapphire lens is better than that of the aluminum lens and silicon lens, and inferior to that of the beryllium lens and diamond lens, but the number of lenses used is less. In the meantime, performances of sapphire lenses focusing are simulated and thermal effects on lenses are analyzed. Analysis and discussion are carried out under the same conditions as the metal Aluminum ones. The focusing simulation shows that the sapphire lenses can obtain a smaller spot with more intensity. The thermal analysis indicates that the temperature during use of the sapphire lens is much lower than the melting point of sapphire, and the thermal deformation is negligible.